The News at the Ends of the Earth - Blum, Hester (Duke University Press, 2019)
From Sir John Franklin's doomed 1845 search for the Northwest Passage to early twentieth-century sprints to the South Pole, polar expeditions produced an extravagant archive of documents that are as varied as they are engaging. As the polar ice sheets melt, fragments of this archive are newly emergent. In The News at the Ends of the Earth Hester Blum examines the rich, offbeat collection of printed ephemera created by polar explorers. Ranging from ship newspapers and messages left in bottles to menus and playbills, polar writing reveals the seamen wrestling with questions of time, space, community, and the environment. Whether chronicling weather patterns or satirically reporting on penguin mischief, this writing provided expedition members with a set of practices to help them survive the perpetual darkness and harshness of polar winters. The extreme climates these explorers experienced is continuous with climate change today. Polar exploration writing, Blum contends, offers strategies for confronting and reckoning with the extreme environment of the present.